Keefektifan Pembelajaran Berbasis Game untuk Meningkatkan Minat dan Motivasi Belajar Fisika: Metaanalisis - Ngilmi, Nuril; Haliza, Ronandita Laila; Setiaji, Bayu (Indonesian Journal Publisher, 2023)
This study aims to analyze the impact of interest and motivation levels in learning physics using a game-based learning approach. To achieve this goal, we conducted a meta-analysis by reviewing 20 journals from various sources, focusing on the effect of interest and motivation levels on physics learning outcomes after applying game-based learning methods. The results showed overall effectiveness with a summary effect of 64%. The study concluded that Fighter Plane War was the most effective game, while Angry Bird Game was less effective. This journal explores the effectiveness of game-based learning in increasing physics learning interest and motivation in students, involving the implementation of interactive games specifically designed to be fun and engaging. The research method involved an experimental group and a control group to compare learning outcomes as well as students' emotional responses. The research findings showed a significant increase in physics learning interest and motivation in the group using game-based learning. The practical implications of this research can help develop innovative learning strategies to improve the quality of physics education in various educational contexts.